2020
DOI: 10.1016/j.jmig.2020.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Double Disk Excision of Large Deep Endometriosis Nodules Infiltrating the Low and Mid Rectum: A Pilot Study of 20 Cases

Abstract: To report the technique of double disk excision of deep endometriosis nodules infiltrating the mid or low rectum and surgical outcomes. Design: A retrospective case series using data prospectively recorded in the North-West Inter Regional Female Cohort for Patients with Endometriosis database. Setting: University tertiary referral center. Patients: Twenty women managed for large deep endometriosis nodules infiltrating the mid or low rectum. Interventions: Double disk excision using transanal end-to-end anastom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Therefore, a diverting stoma has been used selectively by several teams in the context of preventing a rectovaginal fistula 16 . Several randomized trials have demonstrated the protective role of a preventive stoma in low rectal cancer surgery 17–20 . In patients with no concomitant vaginal excision but this is mainly with regards to anastomotic leakage rather than rectovaginal fistula formation and cannot be extrapolated without proper evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a diverting stoma has been used selectively by several teams in the context of preventing a rectovaginal fistula 16 . Several randomized trials have demonstrated the protective role of a preventive stoma in low rectal cancer surgery 17–20 . In patients with no concomitant vaginal excision but this is mainly with regards to anastomotic leakage rather than rectovaginal fistula formation and cannot be extrapolated without proper evidence.…”
Section: Discussionmentioning
confidence: 99%
“…An alternate approach for excision of larger endometriotic nodules is the double disc excision technique, in which two circular EEA staplers are fired successively. In a pilot study by Namazov et al [29], this technique was used to excise low-and mid-rectal nodules with a mean diameter of 53.4 AE 19.1 mm and mean distance of 66 mm from the anal verge.…”
Section: Conservative Vs Radical Excisionmentioning
confidence: 99%
“…For lesions larger than 3 cm shaving is still a reasonable option, however, it is also appropriate to perform a disc excision utilising either a trans-anal stapler or a hand-sewn repair. Evidence also suggests that for nodules larger than 5 cm a double disc excision is a safe and feasible option for surgeons familiar with this technique ( Namazov et al, 2020 ). When multiple nodules larger than 3 cm are infiltrating the bowel a segmental resection is preferred over multiple different disc excisions, however, this recommendation should not supersede clinical judgment.…”
Section: Perspectivementioning
confidence: 99%